2018
DOI: 10.1249/mss.0000000000001627
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Reduces Dopamine D1R and Increases D2R in Rats: Implications for Addiction

Abstract: These findings support the hypothesis that aerobic exercise results in changes in the mesolimbic pathway that could mediate exercise-induced attenuation of drug-seeking behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 48 publications
7
65
0
1
Order By: Relevance
“…Indeed, D 2 R protein density was subtly increased by wheel running in the DMS, AcC, and AcS compared to sedentary mice (see Figure 2(f)), despite overall trends towards greater density in other striatal subregions that failed to reach statistical significance. This finding is consistent with several reports of mildly increased D 2 R mRNA levels, protein density, and ligand binding affinity in the striatum following periods of exercise [65][66][67][68][69][70][71]. Finally, physical activity status had no impact on the density of D 1 R protein (see Figure 2(i)), which has also been reported in previous literature [70,71].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, D 2 R protein density was subtly increased by wheel running in the DMS, AcC, and AcS compared to sedentary mice (see Figure 2(f)), despite overall trends towards greater density in other striatal subregions that failed to reach statistical significance. This finding is consistent with several reports of mildly increased D 2 R mRNA levels, protein density, and ligand binding affinity in the striatum following periods of exercise [65][66][67][68][69][70][71]. Finally, physical activity status had no impact on the density of D 1 R protein (see Figure 2(i)), which has also been reported in previous literature [70,71].…”
Section: Discussionsupporting
confidence: 92%
“…Exercise increased serum dopamine levels and adrenalectomy prevented this effect and the control of serum TNF levels. Similar recent studies showed that moderate exercise can induce dopamine, which contributes to the mesolimbic reward pathway during exercise (Mitchell et al, 2018; Robison et al, 2018; Rosso et al, 2018), enhances cognition by activating D1-dopaminergic receptors (McMorris, 2016a,b), protects dopaminergic neurons against inflammation-induced degeneration (Wu et al, 2011), decreases oxidative stress and inflammation, and restores renal dopamine D1 receptors function in elderly rats (Asghar et al, 2007). Our results show that dopamine inhibited LPS-induced TNF production of primary culture of splenocytes in a concentration dependent manner.…”
Section: Discussionmentioning
confidence: 64%
“…Results from this and previous studies suggest that exercise may affect one or both of these brain regions that is/are common to the variety of relapse pathways, since exercise has been shown to alter reinstatement due to each of these priming stimuli [5254, 78]. Future research should examine the possible mechanisms involved in driving these behavioral changes, including alterations to the mesolimbic dopamine pathway seen following exercise [55, 56]. Alternatively, it is also possible that exercise facilitated the forgetting of the cocaine-paired chamber, possibly due to memory clearance/degradation resulting from exercise-induced increases hippocampal neurogenesis [90, 91].…”
Section: Discussionmentioning
confidence: 90%
“…Previous rodent studies have confirmed exercise’s ability to reduce the acquisition and escalation of drug preference and self-administration [4550], increase the breakpoint for operant responding for psychostimulants [51], and attenuate other types of primed reinstatement (drug-primed and cue-induced) [5254]. These exercise-induced changes in drug-seeking behavior may be linked to alterations in the mesolimbic dopamine pathway [55, 56], which mediates the rewarding/reinforcing properties of drugs of abuse [57, 58]. Very few studies, however, have investigated the ability of exercise to prevent stress-induced relapse specifically.…”
Section: Introductionmentioning
confidence: 99%